PENGARUH FINACIAL LEVERAGE, FIRM GROWTH, LABA DAN ARUS KAS TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Frans Julius P.S; Rita Anugerah; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of financial leverage, firm growth, profit, and cash flow on financial distress. the population in this study is the manufacturing companies listed in Indonesian Stock Exchange and continuously published financial statement in the period of 2010-2014. The sample was determined by the method of purposive sampling. Criterion for firm with probably of financial distress is a company which has a negative net income more than a year and do not paying dividends. By ommiting companies with some data unavailable, the sample consist of 18 companies. This study uses secondary data obtained from the company’s financial statement in the period 2010 to 2014 obtained from the Indonesian capital market directory and www.idx.co.id and analyzed using SPSS 20. The method of analysis used is logistic regression analysis. The results of this study showed that cash flow has an effect to to predict financial distress in the company with 0.013 significance.. While financial leverage, firm growth, and profit have no effect in predicting financial distress in the company. The results of this research also showed that coefficient determinant is 0,347. This means that the percentage of influence of independent variables on the dependent variable is equal to 34,7%, while the rest of 65.3% influenced by other variables that are not included in this model.Keywords: financial distress, financial leverage, firm growth, profit, cash flow.